2013
DOI: 10.1063/1.4801803
|View full text |Cite
|
Sign up to set email alerts
|

A converging route towards very high frequency, mechanically flexible, and performance stable integrated electronics

Abstract: The ability to realize flexible circuits integrating sensing, signal processing, and communicating capabilities is of central importance for the development of numerous nomadic applications requiring foldable, stretchable, and large area electronics. A key challenge is, however, to combine high electrical performance (i.e., millimeter wave, low noise electronics) with mechanical flexibility required for chip form adaptivity in addition to highly stable electrical performance upon deformation. Here, we describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…[61,62] Figure 2e presents the process flow of a DBG process, which alleviates the problematic dispersing process after conventional grinding. [44] The thickness of the semiconductor layer can be reduced to sub-5 µm if the semiconductor wafers have an etch-stop layer like the epitaxial GaN layer in GaN-on-Si wafer [63,64] or the BOX layer in SOI wafer [45,65] (see Figure 2f as an example). Since the major effort of thinning processes is carried on the backside surface, the front side surface of the semiconductor wafer can be fully protected, which is advantageous for postdevice fabrication, i.e., the transistors and circuits have been fabricated on the semiconductor wafer before the thinning process.…”
Section: Overview Of Fabrication Techniques For Microwave Flexible Trmentioning
confidence: 99%
See 2 more Smart Citations
“…[61,62] Figure 2e presents the process flow of a DBG process, which alleviates the problematic dispersing process after conventional grinding. [44] The thickness of the semiconductor layer can be reduced to sub-5 µm if the semiconductor wafers have an etch-stop layer like the epitaxial GaN layer in GaN-on-Si wafer [63,64] or the BOX layer in SOI wafer [45,65] (see Figure 2f as an example). Since the major effort of thinning processes is carried on the backside surface, the front side surface of the semiconductor wafer can be fully protected, which is advantageous for postdevice fabrication, i.e., the transistors and circuits have been fabricated on the semiconductor wafer before the thinning process.…”
Section: Overview Of Fabrication Techniques For Microwave Flexible Trmentioning
confidence: 99%
“…Besides reports of the undercut etching method to release a layer of fabricated devices from Si, a number of studies on direct thinning of industry foundry fabricated deep-sub-micrometer rigid Si RF MOSFET chip to attain mechanically flexible integrated chips were reported. [45,59,60,65,[83][84][85][86] Benefitting from the small feature sizes of the Si RF MOSFETs, the high-frequency properties of rigid form MOSFETs were passed along to flexible form devices. For example, flexible Si RF MOSFETs at 0.13 µm node show an f T of 118 GHz on a plastic substrate via thinning bulk Si wafer.…”
Section: Si Microwave Flexible Transistorsmentioning
confidence: 99%
See 1 more Smart Citation
“…But even under less critical conditions, and once part production is survived, service loads have to be sustained: Locally, these may be increased by mismatches in thermal (coefficient of thermal expansion) and mechanical properties (Young's modulus) of the embedded system and host material, as several authors have pointed out [12,13]. To compensate mechanical loads originating from such misadjustment, stretchable and flexible electronics are being researched [14].…”
Section: Withstanding the Embedding Processmentioning
confidence: 99%
“…Thus, optimizing the substrate is a possible pathway for better RF circuit operation. In previous studies, improvement of electrical performance of RF devices has been reported by complete removal of handler substrate on SOI wafer and transfer onto thin flexible substrate [10]- [15]. While this approach has been shown to work efficiently, some of the drawbacks are higher number of steps in fabrication, possible RF losses in bonding material, mechanical weakening and overall cost of treatment.…”
mentioning
confidence: 99%